Exploring the features of plants threatening Malaysia's heritage buildings (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
Plants contribute to various functions in landscape design such as shade, ornamentation, food sources and etc. For heritage buildings, the functions of plants are identified as elements that can enhance the heritage value of a building. The presence of plants also harms the stability of heritage buildings. Certain plants have been identified to cause damage such as roof damage, wall cracks, plaster layer damage, stains on the paint layer, paint peeling, gutter and drain blockage, and wooden component damage. Therefore, the objective of this study is to identify the features of plants that threaten heritage buildings. This study used a qualitative research design involving observation and interviews. Observation methods were carried out on 112 masonry heritage buildings listed by the National Heritage Department (JWN). In-depth interviews were conducted with eight (8) registered conservators who possess extensive experience and are actively involved in heritage building conservation. The collected data were analyzed thematically to produce a list of characteristics of plants that contribute to the damage of heritage buildings. The study revealed eight (8) plant characteristics, namely compact canopy, shedding leaves excessively, bearing fruit, dense flowering, creeping root, adventitious root, weak wooded, and wide-crowned tree. This study aims to assist conservators, building occupants, maintenance contractors, and landscape architects in selecting suitable plants for landscaping and environmental design surrounding heritage buildings in Malaysia.
Keywords: Plant characteristics; landscape plants; threatening plants; building conservation; heritage building